2020
DOI: 10.35943/mvmj.2020.21.2.0203
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral ketoconazole and griseofulvin on the fertility of male rabbits

Abstract: Objectives: To investigate possible side effects of ketoconazole and griseofulvin on fertility of clinically healthy male rabbits. Design: Randomized controlled experimental study. Animals: Thirty mature male rabbits. Procedures: Rabbits were randomly allocated into three equal sized groups (10 animals each). The first group served as a control group (received no treatment), the second group received griseofulvin (25 mg/kg B.W) orally for 30 days, and the third group received ketoconazole (50 mg/kg B.W) orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…There is little information in the literature about fungal contamination of boar semen and its persistence during storage [ 16 , 17 ]. The usual conditions of storage before AI (liquid state at 17 °C for several days) represent excellent conditions for the development of fungi, and the extenders do not contain antifungal substances.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information in the literature about fungal contamination of boar semen and its persistence during storage [ 16 , 17 ]. The usual conditions of storage before AI (liquid state at 17 °C for several days) represent excellent conditions for the development of fungi, and the extenders do not contain antifungal substances.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Amer et al (2018) reported that testes of fluconazole medicated cocks showed vacuolated spermatocytes with more widening diameter of seminiferous tubule and loss of spermatocytes inside the dilated lumen of seminiferous tubules. Similarly, Mohamed et al (2020) stated that, the testes of ketoconazole treated animals showed marked interstitial fibrosis and edema with severe tubular degeneration and desquamation of germ cells in lumen and arrested spermatogenesis. Testes of linseed oil supplemented group for 2 weeks after fluconazole administration showed widening in luminal diameter of seminiferous tubules, besides, mildly vacuolated spermatocytes in testes of treated cocks.…”
Section: Effect Of Linseed Oil and Fluconazole On Lh Receptor (Lhr) A...mentioning
confidence: 95%
“…Similar finding has reported that administration of fluconazole at both therapeutic and double therapeutic doses induced a significant decrease in serum testosterone level (Hammad et al, 2018). Moreover, Mohamed et al (2020) found that ketoconazole administration induced a prominent decrease in serum testosterone level in treated rabbits. The different small letters in the same column means that there were significant changes at P <0.05.…”
Section: Effect Of Linseed Oil and Fluconazole On Lh Receptor (Lhr) A...mentioning
confidence: 98%
See 1 more Smart Citation
“…The literature in poor in information about fungal contamination of boar semen and its persistence during storage [11,31]. The usual conditions of storage before AI (liquid state at +17°C for several days) represent excellent conditions for the development of fungi, and the extenders do not contain antifungal substances.…”
Section: Introductionmentioning
confidence: 99%